Facial Emotion Recognition for Imitation in Human-Robot Interaction - Yanç, Ibrahim; Ipek, Aykan; Kayaarma, Selma Yilmazyildiz (Institute of Electrical and Electronics Engineers Inc., 2024)
The importance of human-robot interaction (HRI) is increasing day by day and new studies are being carried out every day. In this study, an animatronic robot face that detects human emotions and can mimic these emotions was designed to increase human-robot interaction. Thanks to rapidly developing technological competencies, serious progress has been made in artificial intelligence and scientific studies in this field. Human emotion analysis plays a vital role in human-robot interaction. Since the ability of traditional algorithms to analyze and classify emotions from real-time images is below the acceptable threshold, machine learning and artificial neural networks methods have emerged. In this work, an original animatronic robot face with 18 degrees of freedom was designed. By training a custom Convolutional Neural Network (CNN) model with a mixed dataset consisting of Fer2013, CKPlus, and Kdef datasets, an accuracy rate of 72% was achieved. This trained model was integrated into the system to detect the emotion from the human face and to mimic the detected emotion. © 2024 IEEE.
9th International Conference on Computer Science and Engineering, UBMK 2024 -- 2024-10-26 through 2024-10-28 -- Antalya -- 204906
Keywords: animatronic robotic face; deep learning; emotion recognition; human-robot interaction